The use of infrared thermography in the identification of pododermatitis in broilers - Jacob,Flavia G. (2016)
ABSTRACT International trade in broiler’ feet, mainly to Asian markets, has demanded better quality control. The objective of this research was to study the suitability of using chicken footpad surface temperature to determine early lesions of pododermatitis. The project was conducted in two houses A1 and A2) in a commercial farm during one production flock. A1 had reused litter of wood shavings and rice hulls, and A2 had a new litter of sawdust. Both houses had positive pressure ventilation. The inner area of the poultry was virtually divided into three quadrants. The footpads were checked for the feet quality, and a degree of pododermatitis was awarded. Thermal images were made to test the surface temperature of the foot and identify inflammation in a total of 30 birds per house, at ages 5, 19, 29, 28 and 40 days of grow-out. Conditions of the rearing environment as well as the surface temperature of the litter, litter moisture, and degree of compression, were recorded. The environment within the houses did not differ. The surface temperatures of the footpad did not differ between the groups. The minimum footpad surface temperatures within the scores were similar, except for the score 3, which did not occur in A1. There was a prevalence of severe injury in the house with a new litter.